Formulasi visi dan misi berbasis nilai islami serta pengaruhnya terhadap loyalitas nasabah: suatu pendekatan pemikiran konseptual dalam konteks perbankan syariah - Putri, Arumingtyas Kusumaning (Maliki Interdisciplinary Journal, 2025)
This article examines the formulation of vision and mission statements in Islamic banking institutions grounded in Islamic values and their influence on customer loyalty. The vision and mission are viewed not merely as strategic management tools but as expressions of spiritual awareness that integrate the principles of amanah (trustworthiness), ʿadl (justice), maslahah (public welfare), and barakah (blessing) into the framework of maqāṣid al-syarī‘ah. By conducting a literature review of strategic management, Islamic economics and Islamic consumer behaviour, the article proposes a conceptual framework termed “Spiritual Strategic Alignment” the alignment of Islamic spiritual values with organisational strategy through authentic vision and mission statements. The model posits that internalising Islamic values in these statements enhances customer trust, thereby fostering enduring loyalty (‘loyalty by faith’) in Islamic banking. This theoretical piece does not present empirical data but lays the groundwork for future empirical research and strategic practice in Islamic banking to strengthen its moral and spiritual identity.